New iron tetrazolate frameworks: synthesis, temperature effect, thermal behaviour, Mössbauer and magnetic studies1. Issue 17 (7th May 2015) - Pimenta, Vanessa; Le, Quang Hoang Hanh; Clark, Lucy; Lhoste, Jérôme; Hémon-Ribaud, Annie; Leblanc, Marc; Grenèche, Jean-Marc; Dujardin, Gilles; Lightfoot, Philip; Maisonneuve, Vincent
<x xml:space="preserve">Abstract</x> Two mixed Fe2+/Fe3+ hybrid fluorides: single crystal structures, Mössbauer spectrometry and magnetic properties.